Tribun Medan's Marketing Communication Strategy in Facing Media Business Competition in the Digital Age - Zulkarnain Rito (UMSU, 2023)
This study aims to analyze the marketing communication strategy of the Medan Tribune in the face of media business competition in the digital era. The theory used in this research is the 4P (Product, Price, Place, Promotion) marketing communication strategy from Kotler combined with SWOT analysis (Strengths, Weakness, Opportunity, Threats). The research method uses a qualitative descriptive approach, with data collection techniques carried out by interviews, observation and documentation. The subjects in this study were the team involved in the marketing communication strategy of the Medan Tribune, namely eight informants. The results showed that the marketing strategy of Tribun Medan entering the digital era was carried out by producing news content made in print, online and social media-based multi-platforms as well as building an online news portal filled with fast, accurate, interesting, and different written and video reports to get public trust, then create a digital activity program and develop a Tribune Event Organizer.